Loss of the imprinted snoRNA mbii-52 leads to increased 5htr2c pre-RNA editing and altered 5HT2CR-mediated behaviour - Doe, Christine M.; Relkovic, Dinko; Garfield, Alastair S.; Dalley, Jeffrey W.; Theobald, David E.H.; Humby, Trevor; Wilkinson, Lawrence S.; Isles, Anthony R. (Human molecular genetics, 2009)
The Prader–Willi syndrome (PWS) genetic interval contains several brain-expressed small nucleolar (sno)RNA species that are subject to genomic imprinting. In vitro studies have shown that one of these snoRNA molecules, h/mbii-52, negatively regulates editing and alternative splicing of the serotonin 2C receptor (5htr2c) pre-RNA. However, the functional consequences of loss of h/mbii-52 and subsequent increased post-transcriptional modification of 5htr2c are unknown. 5HT2CRs are important in controlling aspects of cognition and the cessation of feeding, and disruption of their function may underlie some of the psychiatric and feeding abnormalities seen in PWS. In a mouse model for PWS lacking expression of mbii-52 (PWS-IC+/−), we show an increase in editing, but not alternative splicing, of the 5htr2c pre-RNA. This change in post-transcriptional modification is associated with alterations in a number of 5HT2CR-related behaviours, including impulsive responding, locomotor activity and reactivity to palatable foodstuffs. In a non-5HT2CR-related behaviour, marble burying, loss of mbii-52 was without effect. The specificity of the behavioural effects to changes in 5HT2CR function was further confirmed using drug challenges. These data illustrate, for the first time, the physiological consequences of altered RNA editing of 5htr2c linked to mbii-52 loss that may underlie specific aspects of the complex PWS phenotype and point to an important functional role for this imprinted snoRNA.